FGFR2–BRD4 Axis Regulates Transcriptional Networks of Histone 3 Modification and Synergy Between Its Inhibitors and PD-1/PD-L1 in a TNBC Mouse Model - Lei, Josh Haipeng; Zhang, Lei; Wang, Zhenyi; Peltier, Raoul; Xie, Yusheng; Chen, Ganchao; Lin, Shiqi; Miao, Kai; Deng, Chu-Xia; Sun, Hongyan (Frontiers in Immunology, 2022)
Epigenetic reprogramming is an independent mode of gene expression that often involves changes in transcription and chromatin structure due to tumor initiation and development. In this study, we developed a specifically modified peptide array and searched for a recognized epigenetic reader. Our result demonstrates that BRD4 is not only an acetylation reader but propionylation as well. we also studied quantitative binding affinities between modified peptides and epigenetic regulators by isothermal titration calorimetry (ITC). Furthermore, we introduced the Fgfr2-S252W transgenic mouse model to confirm this acetylation is associated with the activation of c-Myc and drives tumor formation. Targeted disruption of BRD4 in Fgfr2-S252W mouse tumor cells also confirmed BRD4 is a key regulator of Histone3 acetylation. Finally, we developed a tumor slice culture system and demonstrated the synergy between immune checkpoint blockade and targeted therapy in TNBC. These data extend our understanding of epigenetic reprogramming and epigenetics-based therapies.